Pyrethroids Toxicity to Male Reproductive System and Offspring as a Function of Oxidative Stress Induction: Rodent Studies - Zhang, Xu; Zhang, Tongtong; Ren, Xiaohan; Chen, Xinglin; Wang, ShangQian; Qin, Chao (Frontiers in Endocrinology, 2021)
Pyrethroids may be related to male reproductive system damage. However, results of many previous studies are contradictory and uncertain. Therefore, a systematic review and a meta-analysis were performed to assess the relationship between pyrethroid exposure and male reproductive system damage. A total of 72 articles were identified, among which 57 were selected for meta-analysis, and 15 were selected for qualitative analysis. Pyrethroid exposure affected sperm count (SMD= -2.0424; 95% CI, -2.4699 to -1.6149), sperm motility (SMD=-3.606; 95% CI, -4.5172 to -2.6948), sperm morphology (SMD=2.686; 95% CI, 1.9744 to 3.3976), testis weight (SMD=-1.1591; 95% CI, -1.6145 to -0.7038;, epididymal weight (SMD=-1.1576; 95% CI, -1.7455 to -0.5697), and serum testosterone level (SMD=-1.9194; 95% CI, -2.4589 to -1.3798) in the studies of rat. We found that gestational and lactational exposure to pyrethroids can reduce the sperm count (SMD=1.8469; 95% CI, -2.9010 to -0.7927), sperm motility (SMD=-2.7151; 95% CI, -3.9574 to -1.4728), testis weight (SMD=-1.4361; 95% CI, -1.8873 to -0.9848), and epididymal weight (SMD=-0.6639; 95% CI, -0.9544 to -0.3733) of F1 offspring. Exposure to pyrethroids can increase malondialdehyde (SMD=3.3451; 95% CI 1.9914 to 4.6988) oxide in testes and can reduce the activities of glutathione (SMD=-2.075; 95% CI -3.0651 to -1.0848), superoxide dismutase (SMD=-2.4856; 95% CI -3.9612 to -1.0100), and catalase (SMD=-2.7564; 95% CI -3.9788 to -1.5340). Pyrethroid exposure and oxidative stress could damage male sperm quality. Gestational and lactational pyrethroid exposure affects the reproductive system of F1 offspring.